A Novel MEMS Parallel-beam Acceleration Switch - Zhao, Jian; Jia, Jianyuan; Chen, Guangyan (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
By utilizing the threshold characteristic and nonlinear transversal stiffness of a post-buckling beam with both ends fixed, a novel parallel-beam acceleration switch was designed. The dynamic model of the switch subjected to multi-forces was established by using post-buckling theory of beams, the damping force was calculated using the Reynolds equations, and the tip-to-drain contact was modeled by elastic Hertz theory. The good threshold characteristic, high contact reliability and anti-jamming performance of the switch were showed after the dynamic numerical simulation. The effect of the damping force and the contact force on the reliability of the switch was analyzed. The response time is less than 6ms when the switch is triggered by a threshold acceleration a c =25g, and the switch cut off quickly when the acceleration is under a d =5g. Therefore, the feasibility of applying the post-buckled beam in designing the acceleration switches was validated